Listen, slowly - Lai, Thanhha (Harper, an imprint of HarperCollinsPublishers, 2015)
Assisting her grandmother's investigation of her grandfather's fate during the Vietnam War, Mai struggles to adapt to an unfamiliar culture while redefining her sense of family.